1966
DOI: 10.1149/1.2424022
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Anodic Films Formed on Reactively Sputtered Tantalum

Abstract: The technique of reactive sputtering has been used for producing tantalum films with various concentrations of interstitial additives like oxygen, carbon, nitrogen, and hydrogen. A number of compounds between tantalum and these nonmetallic elements also have been deposited. The dielectric properties of anodic films on the tantalum formed in an aqueous solution of citric acid have been related to the composition of the tantalum. It was found that the capacitance density of 130v anodic films remains unaffected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…However, Pavlovic (21) reported the dielectric constant of ~-Ta20~ ceramic to be 24.1 at room temperature and 100 kHz. Gerstenberg found an average value of dielectric constant for anodic films of 21.7 (22). There is clearly a strong tempera-) unless CC License in place (see abstract).…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…However, Pavlovic (21) reported the dielectric constant of ~-Ta20~ ceramic to be 24.1 at room temperature and 100 kHz. Gerstenberg found an average value of dielectric constant for anodic films of 21.7 (22). There is clearly a strong tempera-) unless CC License in place (see abstract).…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The role played by oxygen in determining the properties of sputtered tantalum films has been the subject of considerable study over recent years (Gerstenberg and Calbick 1964;Maissel 1962;Steidel and Gerstenberg 1969;Westwood and Livermore 1970;Westwood and Waterhouse 1971). Its importance in the formation of P-Ta (Read and Altman 1965) now appears to be well established (Westwood and Livermore 1970;Westwood and Waterhouse 1971 ;Waterhouse et al 1971) but the electrical properties, specifically its negative temperature coefficient of resistance (TCR), are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Its importance in the formation of P-Ta (Read and Altman 1965) now appears to be well established (Westwood and Livermore 1970;Westwood and Waterhouse 1971 ;Waterhouse et al 1971) but the electrical properties, specifically its negative temperature coefficient of resistance (TCR), are not well understood. Gerstenberg and Calbick (1964) suggested that the conduction mechanism might be "activated" i.e., of the form…”
Section: Introductionmentioning
confidence: 99%
“…Their method provided an average value of P over an area of 25 cm2 and they reported considerable variations in a with position on this sample. Gerstenberg and Calbick (1964) also reported increasing oxygen content of tantalum films as a became increasingly negative. Although they reported that the films always con-sisted of the b.c.c.…”
Section: Discussionmentioning
confidence: 88%
“…Coulometric measurements have been used previously by Gerstenberg (1966) to determine the oxygen content of Ta films but there appear to be inconsistencies in his analysis. For example, although he obtained values off less than unity in some samples, he gives a value for the atomic percent oxygen P. For those samples with f larger than unity, the values of P calculated by Gerstenberg (1966) are different from those obtained by the substitution of his data in the equation presented in this work.…”
Section: This Work Bulk Tamentioning
confidence: 99%